Efficiency vs. the level of per capita income of urban-rural municipalities in Poland - Jarosław Olejniczak (e-Finanse: Financial Internet Quarterly, 2019)
The basic objective of the work was to verify the hypothesis regarding the existence of the correlation between the income potential of the municipalities and the efficiency (relative) of their activity. The basis for such a hypothesis were some concerns as to the validity of the assumed system of funding territorial local governments in Poland- in particular in the area of fiscal transfers. A nonparametric method for the evaluation of relative efficiency - the DEA CCR-O was used in the research. Then the correlation between efficiency scores and local government revenues per capita was measured. The study includes 573 urban-rural municipalities in Poland in the years 2009, 2013, and 2016. As variable 'input' expenditures per-capita were adopted. As 'outputs', 13 variables describing the basic areas of municipal activity were adopted. The results of the conducted analyses point to the existence of a correlation between the commune's revenue level and the effectiveness of its functioning. In the whole of the analysed period, the correlation fluctuated around -0.34 to - 0.42 for total pc revenues and -0.26 to -0.32 for pc own revenues.
Keywords: H2; H71; 330; DEA; local government; revenues